Analysis of Hashtag Utilization Based on Campaigns on the Instagram Account of the Ciliwung Depok Community - Dian Nurdiansyah; Shafa Kamiliya; Muslim Muslim (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Technological advances have brought about major changes in the world of media communication, influencing the way we interact, obtain information, and share content. The internet has become the main pillar of today's communication revolution. With easier and faster internet access, information can now be disseminated in real time to all corners of the world. The emergence of broadband technology, 5G networks, and satellite-based internet has further enhanced accessibility, even in areas that were previously difficult to reach. The rise of Instagram has provided an opportunity for environmental conservation communities to continue their advocacy efforts, and this has become a tangible example of the development of Digital Communication. The research conducted focuses on the use of hashtags in campaign types on Instagram. This research method employs a qualitative descriptive approach and a simple experiment using the tools slice.id. Data collection techniques include observation, interviews, and document studies from previous research conducted by the researchers and other researchers relevant to the study. The Ciliwung Depok Community is a community that plays a significant role in raising public awareness about the importance of preserving river ecosystems. The Ciliwung Depok Community is not involved in any political agenda; it is an independent NGO established to address concerns about the increasing transformation of the Ciliwung River from a source of life into a source of problems.